Drosophila CLASP is required for the incorporation of microtubule subunits into fluxing kinetochore fibres - Maiato, H (2005)
The motion of a chromosome during mitosis is mediated by a bundle of microtubules, termed a kinetochore fibre (K-fibre), which connects the kinetochore of the chromosome to a spindle pole. Once formed, mature K-fibres maintain a steady state length because the continuous addition of microtubule subunits onto microtubule plus ends at the kinetochore is balanced by their removal at their minus ends within the pole. This condition is known as 'microtubule poleward flux'. Chromosome motion and changes in position are then driven by changes in K-fibre length, which in turn are controlled by changes in the rates at which microtubule subunits are added at the kinetochore and/or removed from the pole. A key to understanding the role of flux in mitosis is to identify the molecular factors that drive it. Here we use Drosophila melanogaster S2 cells expressing alpha-tubulin tagged with green fluorescent protein, RNA interference, laser microsurgery and photobleaching to show that the kinetochore protein MAST/Orbit - the single CLASP orthologue in Drosophila - is an essential component for microtubule subunit incorporation into fluxing K-fibres.